Optical properties of (ZnTiO3)/Epoxy Nanocomposite Thin films - Alqaicy, Warqaa Adnan; Abdullah, Sawsan H.; Mustafa, Falah I.; Kh.Ateia, Khalid; M.Ibraheem, Amnah (International Journal of Scientific Research and Management (IJSRM), 2018)
Two layers of epoxy reinforced with nano- Zinc Tetanet (ZnTiO3) uniform thin films have been prepared using a spin coating technique on glass floors, dispersion and magnetic stirring techniques are used to prepare the nanocomposites, FTIR was employed to aid interpretation of results with a fixed thickness and proportions by weight (0Wt%,1Wt%,2Wt%,3Wt%,4Wt%) ZnTiO3additives.The optical characteristics were studied by measuring the transmittance and absorbance spectrometry as a function of the wavelength (200-1100) nanometers. The results of the transmittance were very high, and high transparency in infrared (IR) radiation was measured by the FTIR and UV-VIS measurements. The optical properties included the calculations of the energy gap; some optical constants were also carried out, which included absorption coefficient making it  Suitable for applications of solar cells